The drug information center: a central piece to evidence-based decision making - Andréa C. SFORSIN; Vanusa B. PINTO; Tázia L. CASTRO; Graziela C. SILVA; Gustavo R. SANTOS; Guilherme A. CARNEIRO; Tiago ARANTES; Daiana A. SALES; Maria A. FALCÃO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: To describe the profile of the requests made to the drug information center by health professionals, over the last seven years, in a tertiary teaching hospital. Methods: This is a retrospective descriptive study that analyzed the request made to a Drug Information Center of the biggest hospital complex in Latin America over 2015 to 2021. The requests were analyzed in terms of their subject, time to answer, Anatomical Therapeutic Classification of drugs and inquirer professional. Results: The results demonstrate that the drug information center received and answered 3,442 queries. The number of questions has grown over the years. The time to answer the questioners was mostly less than 1 hour (67%). The majority of the calls were made by pharmacist (45.3%) and nurses (41.6%). The queries from health professionals were mostly about administration (37%), stability (19%), standardization in the institution (11.3%), indication (5.7%) and they referred mainly to agents classified as J - anti-infectious for systemic use (21.2%), B - blood and hematopoietic organs (15.7%), N - nervous system (14.2%), A - Digestive system and metabolism (12.9 %). Conclusion: Due to the high demand in the sector, the importance and recognition of the drug information center in the hospital environment is highlighted. The drug information center has provided na essential information search service in order to respond to the demands of healthcare professionals. Always focused on the best and most accurate information, to promote safe and reliable practices for all patients. With potential to guarantee the patient safety.